Herbicidal Potential of Drechslera spp. Culture Filtrates Against Parthenium hysterophorus L. - Javaid,Arshad (Instituto de Investigaciones Agropecuarias, INIA, 2011)
Herbicidal activity of culture filtrates of four Drechslera spp., namely D. australiensis (Bugnic.) Subram. & B.L. Jain, D. biseptata (Sacc. & Roum.) M.J. Richardson & E.M. Fraser, D. hawaiiensis Bugnic. ex M.B. Ellis, and D. holmii (Luttr.) Subram. & P.C. Jain, prepared in malt extract broth was investigated against parthenium weed (Parthenium hysterophorus L.) in both laboratory bioassays and pots. In laboratory bioassays, the effect of original (100%) and diluted (50%) culture filtrates of the four Drechslera spp. was studied on parthenium germination and seedling growth in 90 mm diameter Petri plates. Original culture filtrate of all the four Drechslera species significantly reduced germination, shoot length, shoot fresh biomass, root length, and root fresh biomass of parthenium seedlings by 43 to 77%, 77 to 82%, 69 to 82%, 90 to 92%, and 67 to 83%, respectively, as compared to the control. In pot trials, foliar application of original fungal culture filtrates was carried out on 1-wk and 2-wk old parthenium seedlings. Culture filtrates of all the four Drechslera spp., except D. holmii, markedly reduced parthenium shoot dry weight. Two-week-old plants were more susceptible to foliar spray than the 1-wk old plants. There was a 13 to 55% and 28 to 65% reduction in shoot dry weight of 1-wk and 2-wk old parthenium plants, respectively, due to culture filtrates of various Drechslera spp. The present study concludes that Drechslera spp. culture filtrates can be used as alternative herbicides for parthenium weed management.